Cytochrome P450-mediated bioactivation of the chemotherapeutic cyclophosphamide for use in cancer gene therapy (Innovation & Development in Engineering and Applied Science, 2025)
This review examines the role of cytochrome P450 enzymes in the bioactivation of the chemotherapeutic agent cyclophosphamide (CPA) for use in cancer gene therapy. The study explores specific cytochrome P450 enzymes, such as CYP2B6, CYP2C9, and CYP3A4, responsible for metabolizing CPA into its active form, highlighting its potential in suicide gene therapy or GDEPT. The review also discusses genetic modifications made to improve the catalytic efficiency of these enzymes and addresses the challenges and future directions of integrating GDEPT with other cancer therapies to improve treatment specificity and efficacy.
Keywords: GDEPT; Cyclophosphamide; Gene Therapy; Cytochromes P450; Chemotherapy; Bioactivation; Genetic Modification